Characterization of Choline Transporters in the Human Placenta over Gestation - Baumgartner, Heidi K. (Placenta, 2015)
INTRODUCTION: The developing fetus relies on the maternal blood supply to provide the choline it requires for making membrane lipids, synthesizing acetylcholine, and performing important methylation reactions. It is vital, therefore, that the placenta is efficient at transporting choline from maternal to fetal circulation. Although choline transporters have been found in term placenta samples, little is known about what cell types express specific choline transporters and how expression of the transporters may change over gestation. The objective of this study was to characterize choline transporter expression levels and localization in the human placenta throughout placental development. METHODS: We analyzed CTL1 and −2 expression over gestation in human placental biopsies from 6 to 40 weeks gestation (n=6–10 per gestational window) by immunoblot analysis. To determine the cellular expression pattern of the choline transporters throughout gestation, immunofluorescence analysis was then performed. RESULTS: Both CTL1 and CTL2 were expressed in the chorionic villi from 6 weeks gestation to term. Labor did not alter expression levels of either transporter. CTL1 localized to the syncytial trophoblasts and the endothelium of the fetal vasculature within the chorionic villous structure. CTL2 localized mainly to the stroma early in gestation and by the second trimester co-localized with CTL1 at the fetal vasculature. DISCUSSION: The differential expression pattern of CTL1 and CTL2 suggests that CTL1 is the key transporter involved in choline transport from maternal circulation and both transporters are likely involved in stromal and endothelial cell choline transport.